AB0032 Bone destruction in rheumatoid synovia. (1st June 2001) - Taniguchi, K; Kuga, Y; Ito, K; Uchida, S; Uchida, T; Oda, H
Abstract : Background: Rheumatoid Arthritis (RA) is characterised by severe and irreversible bone destruction in affected joints on its last stage. On the other hand, bone absorption by osteoclasts may be a natural physiological phenomenon as bone remodelling in mature manhood. Throughout our life, bone is constantly renewed with the process of old bone removing and new bone supplement. Osteoclasts are derived from the hematopoietic granulocyte/macrophage colony forming units, which also become to monocytes and macrophages, and their progenitors move from bone marrow to bone surface through the circulation or direct migration, and differentiate to functional mature osteoclasts with stimulation of some cytokines and/or direct contact. In RA, or another bone destructive disease, activated osteoclasts certainly have a critical role in bone destruction. But, is that all? How bone is broke down in RA? We have speculation that some cells derived from rheumatoid synovia were activated by inflammatory cytokines abundant in the joint of RA and take a significant role in the destruction of the bone. Objectives: To elucidate what mechanism is there, we have observed the pannus-bone junctions in detail. Methods: The specimens of the destructive bone derived from the RA patients under arthroplasty with their consent. Tissue sections from the pannus-bone junctions at sites of bone erosion were examined by hematoxylin-eosin staining, tartrate-resistant acid phosphatase (TRAP) staining, and electron microscopy. Synovial tissues were also examined immunohistochemically. Results: The specimens of the destructive bone derived from the RA patients showed that there were many not-classical osteoclasts in the area of bone erosions. Cells in the erosive front of RA are divided in four groups, the authentic osteoclasts, mononuclear osteoclasts, fibroblast-like cells and monocytes. The electron microscopy observations revealed that the fibroblast-like cells certainly have some contact with bone matrix. TRAP-positive cells and vitronectin receptor -positive cells were seen in frozen sections of synovial membrane from the patient with RA. Conclusion: Our result showed that not only authentic osteoclasts, but the mononuclear cells and fibroblast-like cells were activated and have some role in bone destruction of RA. References: Arthritis Rheum. 1984;27:968–75 Ann Rhuem Dis. 1993;52:133–7